2022
DOI: 10.1101/2022.11.07.515454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Allosteric activation of cell wall synthesis during bacterial growth

Abstract: The peptidoglycan (PG) cell wall protects bacteria against osmotic lysis and determines cell shape, making this structure a key antibiotic target. Peptidoglycan is a polymer of glycan chains connected by peptide crosslinks, and its synthesis requires precise spatiotemporal coordination between glycan polymerization and crosslinking. However, the molecular mechanism by which these reactions are initiated and coupled is unclear. Here we use single-molecule FRET and cryo-EM to show that an essential PG synthase (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
(87 reference statements)
1
4
0
Order By: Relevance
“…We conclude that MreC is required for proper midcell localization and for elongasome PG synthesis by the bPBP2b:RodA synthase. This result is consistent with the previous conclusion that MreC allosterically activates the GT/TP activity of RodA:PBP2 in the PG elongasome of E. coli (16,67,105).…”
Section: Bpbp2b Localization Becomes Diffuse and Circumferential Move...supporting
confidence: 93%
“…We conclude that MreC is required for proper midcell localization and for elongasome PG synthesis by the bPBP2b:RodA synthase. This result is consistent with the previous conclusion that MreC allosterically activates the GT/TP activity of RodA:PBP2 in the PG elongasome of E. coli (16,67,105).…”
Section: Bpbp2b Localization Becomes Diffuse and Circumferential Move...supporting
confidence: 93%
“…Since our sample is active in vitro, we assume that substrate binding by Lipid II might play a key role in the interconversion of the two states. Recently, a study on RodA-PBP2 reported a similar upswinging mechanism 22 , which indicates that the concept of regulating the TP activity via restricting its access to the PG layer might be conserved between the divisome and the elongasome. However, significant differences exist between divisome and elongasome regarding the conformation before the upswinging motion and most likely also between the signals required to initiate this conformational change.…”
Section: Comparison With Roda-pbp2 Structures and Structure Predictionsmentioning
confidence: 87%
“…Lipid II used to monitor glycosyltransferase activity of the protein complex was dried using a nitrogen stream and dissolved in an equal volume of dimethyl sulfoxide (DMSO). The reaction and detection of glycan strands was adopted from previously published protocols 5,[20][21][22] . Briefly, PaFtsWIQLB and EcFtsWIQLB were mixed at a final protein concentration of 1 µM in 10µL with 1 µL 10x Reaction Buffer (500 mM Tris pH 7.5, 200 mM MnCl2), 1 µL DMSO and 1 µL Lipid II and incubated for 30 min at 25°C.…”
Section: Transglycosylase Activity Assaymentioning
confidence: 99%
“…One intriguing question that remains unanswered is how E FtsN's binding to the AWI FtsL-FtsI complex is transmitted to the active site of FtsW located in the periplasm proximal to the membrane. Recently, Shlosman et al 34 proposed that an extended open conformation of PBP2 (promoted by MreC) activates RodA. Jan Lowe's group used cryo-EM and found that PaFtsI complexed with PaFtsQLB exists in a partially open form with its TP domain heading away from PaFtsW but short of reaching the PG layer 35 .…”
Section: Discussionmentioning
confidence: 99%